COLLABORATION OF PARENTS AND TEACHERS – FROM THEORETICAL ASSUMPTIONS TO THEIR PRACTICAL IMPLEMENTATION (THE CASE OF POLISH SCHOOL ABROAD) - Hruzd-Matuszczyk, Alicja (The Modern Higher Education Review, 2018)
The study is an attempt at characterizing the theoretical assumptions concerning the collaboration of teachers and parents which are implemented in the space of school. What is outlined in the article is the cooperation in the space of the Polish community living abroad in the culturally diversified environment. The proper functioning of school depends on cooperation between teachers, students and parents. The effectiveness of the cooperation of parents and teachers is determined by many complex factors. In this study, the principles and problems are brought closer that arise from asymmetric positioning of educational subjects (students, teachers and parents), which generates different needs and ideas in mutual cooperation. This is exemplified here by the Polish-language school education system, whose activity reflects the needs and possibilities of the Polish communities in culturally heterogeneous European environments in the creation and functioning of Polish-speaking educational institutions and the involvement of the community gathered around these schools.